2017
DOI: 10.3892/ol.2017.6368
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and the risk of cancer

Abstract: Abstract.Cancer is a multifactorial disease, and imbalances of the immune response and sex-associated features are considered risk factors for certain types of cancer. The present study aimed to assess whether ankylosing spondylitis (AS), an immune disorder that predominantly affects young adult men, is associated with an increased risk of cancer. Using the Taiwan National Health Insurance Research Database, a cohort of patients diagnosed with AS between 2000 and 2008 who had no history of cancer prior to enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In contrast, while the incidence of cancer was much higher in AS patients first diagnosed at 60‐80 years of age, there was no difference between patients with and without AS. Similar findings have been observed previously in the literature 12,13 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, while the incidence of cancer was much higher in AS patients first diagnosed at 60‐80 years of age, there was no difference between patients with and without AS. Similar findings have been observed previously in the literature 12,13 …”
Section: Discussionsupporting
confidence: 93%
“…A significant increase in the risk of prostate cancer was observed in male AS patients. Increased risk of prostate cancer was also observed in a Taiwanese cohort (standardized incidence ratio [SIR] 1.64, 95% CI: 1.04‐2.47) 12 and a Korean cohort of AS patients (SIR 1.97, 95% CI: 1.59‐2.35) 14 . Given AS disproportionally effects males, the role of androgens has been investigated as a potential contributor to the increased risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have no data regarding whether HLA‐B*27:05 is associated with other systemic irAEs caused by atezolizumab or whether HLA‐B*27:05 increases the risk of irAEs induced by other ICPIs, such as CTLA‐4 or PD‐1 inhibitors. In addition, because patients with HLA‐B27 or ankylosing spondylitis have an slightly increased risk of hematologic malignancy or systemic cancer, 39,40 it is also necessary to analyze the prevalence of HLA‐B27 in the control cancer patients. Until then, our data suggest that HLA‐B*27:05 might be a risk factor gene for CNS‐irAEs induced by atezolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no definite evidence linking AS and thymoma, 2 studies in Taiwan reported that the incidence of tumors in AS patients to be 1.15 times that of patients without AS. [ 9 ] The incidence of gynecologic tumors, head and neck tumors, and bladder cancer in AS patients is 1.97 to 3.22 times that of non-AS patients. The risk of liver cancer and lung cancer is significantly higher in AS patients than in controls.…”
Section: Discussionmentioning
confidence: 99%